Genetic studies of quality traits in tomato (Solanum lycopersicum L.) under low temperature - Droka, Dechin; Kumar, Raj; Joshi, Subodh; Yadav, RK (Vegetable Science, 2012)
Tomato (Solanum lycopersicum L.) is an important vegetable crop due to its high nutritional and antioxidant properties. The pulp and juice are digestible, promote gastric secretion and help in blood purification. Though a lot of work has been reported regarding inheritance of quantitative characters in tomato (Megha et al. 2005; Singh 2005), but much attention has not been paid to know the inheritance of qualitative traits that to under low temperature. Heterosis breeding will be useful in the development of varieties/hybrids having high fruit quality traits. The generation mean analysis has a general application for genetic evaluation of any population irrespective of gene frequency and mating design. This provides not only valid estimate of gene effects but also an ambiguous test for presence or absence of epistasis. The knowledge of gene effects controlling the inheritance of characters under low temperature helps in choosing the appropriate breeding method for crop improvement.